2017
DOI: 10.17512/ios.2017.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Wastewater from Animal Rendering Plant

Abstract: In this study, wastewater originating from a post-slaughter waste management plant, the main activity of which is the recovery of other than hazardous wastes of animal origin and wastes from the agri-food processing, were analyzed. The main substrates processed in the installation include post-slaughter wastes and wastes from the agri-food processing, like e.g.: waste animal tissue, raw materials and products unsuitable for consumption and processing originating from the food, dairy, bakery and confectionery i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…3.5%. Therefore, the content found in the present study can be considered low, and, surprisingly, is more similar to values found in sludge from meat processing wastewater (Rodziewicz et al 2017 ). When analyzing the content of selected metals in the studied sewage sludge, the following mean values were found (in mg/kg dry weight): Cd 6, Cr 75, Cu 220, Ni 17, Pb 173, and Zn 1086 (Table 1 ).…”
Section: Resultssupporting
confidence: 86%
“…3.5%. Therefore, the content found in the present study can be considered low, and, surprisingly, is more similar to values found in sludge from meat processing wastewater (Rodziewicz et al 2017 ). When analyzing the content of selected metals in the studied sewage sludge, the following mean values were found (in mg/kg dry weight): Cd 6, Cr 75, Cu 220, Ni 17, Pb 173, and Zn 1086 (Table 1 ).…”
Section: Resultssupporting
confidence: 86%